Hepcidin and fungal infections: The liver fights back - Karl Kuchler (Cell Reports)
Arekar et al. demonstrate that the liver peptide hepcidin holds therapeutic promises for treating invasive fungal infections by Candida albicans.1 A hepcidin agonist improves infection outcome because it protects from renal pathology by diminishing iron bioavailability in kidneys.